2007
DOI: 10.1210/jc.2006-2223
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Adrenal Axis Function and the Cellular Immune Response in Former Preterm Children

Abstract: The data suggest that preterm delivery may be associated with altered endocrine and immune functions well into late childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 40 publications
7
65
4
Order By: Relevance
“…We found GC-stimulated 11␤-HSD-1 activity to correlate inversely with birth weight (the degree of SGA) and GA (prematurity). Enhanced GC-stimulated 11␤-HSD-1 activity in children with shorter gestation and lower birth weight SDS is in agreement with previous reports of cortisol levels in SGA (21,22,56). However, this finding did not correlate with age, indicating that the process is not progressive, but rather programmed from birth.…”
Section: Discussionsupporting
confidence: 91%
“…We found GC-stimulated 11␤-HSD-1 activity to correlate inversely with birth weight (the degree of SGA) and GA (prematurity). Enhanced GC-stimulated 11␤-HSD-1 activity in children with shorter gestation and lower birth weight SDS is in agreement with previous reports of cortisol levels in SGA (21,22,56). However, this finding did not correlate with age, indicating that the process is not progressive, but rather programmed from birth.…”
Section: Discussionsupporting
confidence: 91%
“…School aged children born very preterm or with very-low-birth-weight (VLBW; < 1500 g) show lower diurnal cortisol profiles (Wadsby et al, 2014), faster decreasing cortisol levels in the evening , and decreased salivary cortisol responses to social stress (Buske-Kirschbaum et al, 2007), which is also consistent with findings in adults (Kaseva et al, 2014). Relatedly, boys born very preterm exposed to more distressing medical procedures had lower diurnal cortisol levels at age 7 (Brummelte et al, 2015).…”
Section: Maurersupporting
confidence: 63%
“…Two prior studies for instance found higher cortisol levels right at awakening in preterm compared to full-term children aged 8 to 12 years (Buske-Kirschbaum et al, 2007), particularly in girls (Quesada et al, 2014). There are three possibly relevant factors for these inconsistent findings.…”
Section: Differences In Salivary and Hair Glucocorticoids Between Vermentioning
confidence: 96%
See 1 more Smart Citation
“…There is emerging evidence that stressful prenatal and neonatal factors, such as preterm birth, may imprint a pattern of physiological activity in the developing brain, known as foetal programming [64]. The immune system and the hypothalamus-pituitary-adrenal stress-regulating system are found to be especially vulnerable to long-term alteration in children born preterm [65]. We therefore speculate that an altered stress-response might contribute Pegboard was associated with higher FA in CST (p<0.02), and poorer performance on…”
Section: Discussionmentioning
confidence: 99%